Revising Australian Pristomerus (Hymenoptera, Ichneumonidae, Cremastinae): species with a tooth on the hind femur - Klopfstein, Seraina (Zootaxa, 2016)
The Australian insect fauna is among the least-well studied in the world, and conservative estimates state that 75% of the species still await description. In the more species-rich groups, this percentage might be even larger, which is certainly the case in parasitoid wasps which have received very little attention by taxonomists. The genus Pristomerus of the family Ichneumonidae is distributed worldwide, with most species found in the tropics. Its members attack concealed larvae of small Lepidoptera, and several species are used in biocontrol. Five species have been reported from Australia, all of them endemic, but many more undescribed species are present in various collections.        I here revise Australian Pristomerus, focussing on the species that bear a tooth on the ventral side of the hind femur. Twenty-two species are recorded, 19 of which are described as new: Pristomerus australiensis n. sp., P. bertschmanni n. sp., P. callitrinus n. sp., P. dundeei n. sp., P. flavicephalus n. sp., P. fourecksensis n. sp., P. gracilis n. sp., P. kakaduensis n. sp., P. laetus n. sp., P. luculentus n. sp., P. lunatus n. sp., P. mangiferus n. sp., P. merus n. sp., P. nedkellyi n. sp., P. pellicius n. sp., P. periculosus n. sp., P. stellatus n. sp., P. tenebrosus n. sp., and P. venustus n. sp. A dichotomous key and an online interactive key to the known Australian species with a tooth on the hind femur are provided, including photographs of all the species.        The origin of the considerable number of Australian Pristomerus species remains unclear. They might represent Southern relict elements with affinities to South American taxa, or their ancestors might have immigrated from the Paleotropics in more recent times; this question can only be solved with a dated phylogeny of the genus. However, support for a Palaeotropic origin of at least a good portion of the taxa comes from their current distribution, as the Australian Pristomerus are found to be most diverse in the tropical habitats of Northern Queensland and the Northern Territories.